Identifikasi Telur Soil Transmitted Helminths Pada Lalapan Mentimun Di Warung Makan Jalan Abdul Kadir Kota Makassar - Andri Setiawan; Andi Indrawati; Jurnal Syarif (Jurnal Media Laboran, 2017)
Soil Transmitted Helminths are intestinal nematodes which in their life cycle require soil for the ripening process. Worm problems associated with this worm infection are still commonly found. The rate of contamination of Soil Transmitted Helminths in vegetables is also still quite high. The process of processing and washing raw vegetables is not ready to eat, making it easier to transmit worm eggs to humans. Cucumber is one suitable substrate because it is often used as fresh vegetables. The purpose of this study is to determine the presence or absence of Soil Transmitted Helminths eggs in cucumber vegetables at food stalls in Jalan Abdul Kadir, Makassar City and the benefits of this research as information for the public about eggs Soil Transmitted Helminths that have an impact on the health problems of the human body. The type of research conducted is descriptive laboratory observation, which is to carry out laboratory tests to identify the Soil Transmitted Helminths eggs in cucumber vegetables at a food stall in Jalan Abdul Kadir, Makassar City. From the analysis of 10 samples of Cucumber vegetables, it shows that in the sample code (A), (B), (C), (D), (E), (F), (G), (H), (I), and (J), negative. So it can be concluded that there is no contamination of Soil Transmitted Helminths eggs in 10 samples of cucumber vegetables that have been studied. Suggestions to the public to remain careful in choosing or processing cucumbers which will be used as vegetables.